Genetic structure of khon mueang populations along a historical yuan migration route in northern thailand - Kutanan W. (2014)
The genetic structure and diversity of the Khon Mueang, who constitute the majority of the current northern Thai populations, is poorly understood. In present study, 433 unrelated individuals from 10 Khon Mueang villages, located in different geographic areas along historical Yuan migration route, were analyzed using the mtDNA hypervariable region (HVR) 1 and 17 Y chromosome short tandem repeats (Y-STRs) as markers. The studied populations from the Chiang Mai-Lamphun basin showed the evidence of demographic expansion and gene flow process in this area. Genetic structure of the geographically diverse Khon Mueang was driven by geography, while genetic differentiation of Chiang Mai-Lamphun populations was shaped by genetic exchange with the neighbouring populations in the area. Contrasting patterns of mtDNA and Y chromosome variations, influenced by sex-bias rates of migration and admixture, suggests that male and female Khon Mueang do not have identical demographic histories.